The Development of Competency Test Material (MUK) Motorcycle Periodic Maintenance Cluster Industrial Based LSP P1 SMK - Budiyanto, Aris; Samsudi, Samsudi; Sutopo, Yeri (Journal of Vocational and Career Education, 2023)
The industry has a different view of prospective workers. Competency certificates recommended by third and second parties (LSP P3 and LSP P2) have stronger legitimacy than LSP P1 SMK. Quality assurance of the implementation of competency certification tests through the development of competency test materials needs to be improved.Specifically, this study aims to: Develop MUK; Find out its eligibility; Find out its practicality; Find out the internal validity and reliability of the Multiple Choice Questions; Find out its effectiveness; and Find out the effectiveness of the utilization of facilities and infrastructure of the Competency Test Site (TUK).This MUK development research uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data analysis used in this study consisted of: Determining eligibility; Determining practicality; Determining the internal validity and reliability of multiple-choice questions; Determining the effectiveness and Determining the effectiveness of the utilization of TUK facilities and infrastructure.The result of the due diligence was included in the criteria of being very eligible. The Practicality Test fell into the criteria of being very practical. The internal validity test of multiple-choice questions showed 77 of 86 valid and the internal reliability test of multiple-choice questions was very high. Effectiveness tests fell under the criteria of being very effective. The effectiveness test of the utilization of TUK facilities and infrastructure was included in the criteria of being very effective.The new findings in this study are, the MUK of motorcycle periodic maintenance cluster industrial based consists of multiple choice test, oral test and demonstration practice tasks adapted to the latest knowledge of motorcycle technology product, the suitability of the required working time (Flat Rate Service Time) and the implementation of the work culture on Safety Talk and 5 Rs (Concise, Neat, Clean, Caring and Diligent).Based on the results of the study, it can be concluded that, the development of MUK is very eligible, practical and effective to be used in improving the quality of the competency certification test of the LSP P1 SMK on Motorcycle Periodic Maintenance Cluster.